2017
DOI: 10.1111/ggr.12193
|View full text |Cite
|
Sign up to set email alerts
|

A Matrix‐Matched Reference Material for Validating Petroleum Re‐Os Measurements

Abstract: This study presents two matrix‐matched reference materials developed for petroleum Re‐Os measurements. We present the Re and Os mass fractions and 187Re/188Os and 187Os/188Os values (ratio of the number of atoms of the isotopes) for repeatedly measured aliquots (ca. 120–150 mg test portions) of the NIST Research Material 8505 (RM 8505) crude oil, and its asphaltene and maltene fractions, and ~ 90 g of homogeneous asphaltene powder isolated from this oil. Measurements were performed using the Carius tube‐isotop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 46 publications
5
21
4
Order By: Relevance
“…The average blanks during this study were 3.4 picogram for Re, and 0.02 picogram for Os. For the present analyses, the measured Re and Os concentrations of homogenised asphaltene isolated from NIST Research Material 8505 (RM 8505) crude oil were 16.128-16.699 parts per billion (ppb, 10 -9 ) and 162.31-166.88 parts per trillion (ppt, 10 -12 ), with 187 Re/ 188 Os and 187 Os/ 188 Os ratios of 571.6-573.2 and 1.612-1.640, respectively (Table 1), consistent with previously published data by Liu and Selby (2018). The Re-Os mass fractions and isotopic compositions of asphaltene fractions from the terrestrial crude oils in the Hailar Basin are presented in Table 2.…”
Section: Samples and Methodssupporting
confidence: 89%
See 2 more Smart Citations
“…The average blanks during this study were 3.4 picogram for Re, and 0.02 picogram for Os. For the present analyses, the measured Re and Os concentrations of homogenised asphaltene isolated from NIST Research Material 8505 (RM 8505) crude oil were 16.128-16.699 parts per billion (ppb, 10 -9 ) and 162.31-166.88 parts per trillion (ppt, 10 -12 ), with 187 Re/ 188 Os and 187 Os/ 188 Os ratios of 571.6-573.2 and 1.612-1.640, respectively (Table 1), consistent with previously published data by Liu and Selby (2018). The Re-Os mass fractions and isotopic compositions of asphaltene fractions from the terrestrial crude oils in the Hailar Basin are presented in Table 2.…”
Section: Samples and Methodssupporting
confidence: 89%
“…Providing temporal constraints on the evolution of a petroleum system within a sedimentary basin is of fundamental importance to exploration targeting by industry. The rhenium-osmium (Re-Os) geochronometer is a promising absolute dating technique for organic-rich rocks and their associated hydrocarbon derivatives (see reviews in Cohen 2004;Stein and Hannah 2015;Li et al 2017;Liu and Selby 2018). Both Re and Os are redox-sensitive and organophilic, and can be enriched in hydrocarbon source rocks, tar sands, crude oil, and bitumen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhenium and the PGE mass fractions are usually measured by ICP-MS with ID method. Some labs use NTIMS for determination of Re (e.g., Markey et al, 2007 ; Liu and Selby, 2018 ). When NTIMS is used, it should be noted that trace amount of Re is probably present in the Pt filament (e.g., Day et al, 2003 ), and thus often Ni filament is applied with Ba(NO 3 ) 2 as an ion emitter.…”
Section: Mass Spectrometric Determinationmentioning
confidence: 99%
“…NIST RM 8505 whole oil and its homogenized powered asphaltene separates were recommended as Re-Os matrix-matched oil RMs by Liu and Selby (2018) . Hurtig et al (2020) also reported Re-Os data for NIST RM 8505 crude oil and another oil RM, NIST RM 1634c.…”
Section: Reference Materials For Data Quality Control Of Re-os and Pgmentioning
confidence: 99%